A study protocol for a randomized controlled trial to assess the efficacy of Baduanjin exercise on older adults with sarcopenia in China - Shengnan Yue; Jing Zhang; Jiaxin Li; Yanwei Hao; Shaofeng Wang; Tianyu Liu; Wen Zhong; Chongli Chen; Fei Wang; Bin Li (BMC Complementary Medicine and Therapies, 2022)
Abstract Background Accompanied by the decline of physiological functions, the decrease of physical activity, and comorbidities, older adults are susceptible to sarcopenia because of accelerated loss of muscle mass. Resistance training is recommended by different clinical practice guidelines. However, most older adults have difficulty in taking recommended high-load resistance training programs, and there are limited exercise options form them. Baduanjin, a traditional Chinese mind-body exercise with relatively low intensity and simple movements, has the potential benefits of improving physical functions and may be feasible in treating sarcopenia and preventing its adverse health outcomes in older patients. With the emergence of the concept of gut-muscle axis, this study aims to determine the efficacy of Baduanjin exercise on Chinese older adults with sarcopenia and explore its underlying mechanism. Methods This is a 24-week, assessor-blinded, randomized controlled trial. Individuals aged 60 to 84 years old will be screened for sarcopenia. 90 participants with sarcopenia will be enrolled and randomly assigned (1:1) into the Baduanjin exercise or resistance training group, and 20 participants without sarcopenia will be set as the non-sarcopenia control group. The primary outcome is the scores of Short Physical Performance Battery. The secondary outcomes are body composition, handgrip strength, walking speed, global cognitive function, and incidence of falls. These outcomes will be assessed at baseline, the 12th week and the 24th week. While stool samples from participants will be collected at baseline and the 24th week for analyzing the abundance of gut microbiome. Data will be analyzed in an intention-to-treat protocol. Discussion The results of this study will determine whether Baduanjin exercise can be an alternative non-pharmacological approach for older adults with sarcopenia. If they can show positive significance, it will promote Baduanjin exercise in clinical practice among these patients and inform further research involving exercise interventions on the optimal types, timing, and intensity to ameliorate sarcopenia for elderly people. Trial registration Chinese Clinical Trial Registry; Registration number: ChiCTR2100051871; Prospectively registered on October 8th, 2021.